Pengaruh Disiplin Siswa dan Sarana Prasarana terhadap Prestasi Belajar Siswa di SMAN 9 Kota Tangerang - Muhammad Asâ€™ad; Nur Soleha (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2019)
The purpose of this study is to analyze the influence of Student Discipline and Infrastructure Facility to Student Achievement Achievement in SMAN 9 Kota Tangerang Banten. The research method used is quantitative method through the spreading of questionnaires with population number 191 and the sample is 129 respondents, based on slovin formula. Based on the results of research using partial and multiple linear regression analysis with the help of SPSS version 23 shows that partially indicates that the Discipline Students have a positive and significant influence of 30.7% on Student Achievement, partially indicate that the infrastructure has no positive and significant effect of 3.4% against Student Achievement.Partially, both results indicate that student discipline and facilities of Infrastructure are jointly tested by F test proved to have a positive and significant influence on Student achievement siswadan influence magnitude seen from niali coefficient of determination (RÂ²) is 9.4%